The learning pathways of Brazilian surf coach developers - Brasil, V. Z.; Ramos, V.; Milistetd, M. (International Journal of Sports Science & Coaching, 2018)
The purpose of this study was to explore the learning pathways of five Brazilian surf coach developers, in order to understand how they became coach developers. A case study was conducted with five surf coach developers working in the sport participation context, and linked to a legally organized Brazilian surf federation. Three main research topics guided the semi-structured interviews: participants` experiences as a surfer, as a surf coach, and as a coach developer. Data were analyzed using thematic analysis to explore the participants` perceptions of the experiences around becoming a surf coach developer. The study revealed a pattern of formative experiences for the participants, across their lives and careers. Their experiences as a surfer and as a surf coach, as well as their exposure to the surfing environment and their contact with significant others, influenced in their engagement in surfing and in the surf coach context; leading them eventually to the desire to share knowledge with others. Becoming a surf coach developer in this study corresponded to a mutual socialization process across a lifetime. This process was marked by situated socio-cultural aspects of different life phases, strongly influenced by the social relations established in immediate contexts (family) and with other specific groups (surfers, coaches, and developers).